Loss of the extracellular matrix protein Perlecan disrupts axonal and synaptic stability during Drosophila development - Ellen J Guss; Yulia Akbergenova; Karen L Cunningham; J Troy Littleton (eLife, 2023)
Heparan sulfate proteoglycans (HSPGs) form essential components of the extracellular matrix (ECM) and basement membrane (BM) and have both structural and signaling roles. Perlecan is a secreted ECM-localized HSPG that contributes to tissue integrity and cell-cell communication. Although a core component of the ECM, the role of Perlecan in neuronal structure and function is less understood. Here, we identify a role for Drosophila Perlecan in the maintenance of larval motoneuron axonal and synaptic stability. Loss of Perlecan causes alterations in the axonal cytoskeleton, followed by axonal breakage and synaptic retraction of neuromuscular junctions. These phenotypes are not prevented by blocking Wallerian degeneration and are independent of Perlecan’s role in Wingless signaling. Expression of Perlecan solely in motoneurons cannot rescue synaptic retraction phenotypes. Similarly, removing Perlecan specifically from neurons, glia, or muscle does not cause synaptic retraction, indicating the protein is secreted from multiple cell types and functions non-cell autonomously. Within the peripheral nervous system, Perlecan predominantly localizes to the neural lamella, a specialized ECM surrounding nerve bundles. Indeed, the neural lamella is disrupted in the absence of Perlecan, with axons occasionally exiting their usual boundary in the nerve bundle. In addition, entire nerve bundles degenerate in a temporally coordinated manner across individual hemi-segments throughout larval development. These observations indicate disruption of neural lamella ECM function triggers axonal destabilization and synaptic retraction of motoneurons, revealing a role for Perlecan in axonal and synaptic integrity during nervous system development.